PENGARUH CUSTOMER ENGAGEMENT TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (STUDY KASUS PADA BANK BRI UNIT BELIMBING PADANG) - Regi Erlan Marta; Abror Abror; Okki Trinanda (Universitas Negeri Padang, 2019)
The purpose of this research are to analyze (1) the influence of Customer Engagement and Customer Satisfaction on Customer Loyalty (2) Influence Customer Engagement on Customer Satisfaction. This type research of causative, research was conducted in the city Padang. The population in this Customer Bank BRI Unit. The population in this study customer Bank BRI Unit Belimbing Padang. The sampel use was 200 people using purposive sampling. Types of data in this primer and sekunder. Using SmartPLS versi 3.0. The results of this research show (1) Customer Engagement has a positive and significant on Customer satisfaction (2) Customer Engagement has a positive and significant on Customer loyalty (3) Customer Satisfaction has a positive and significant on Customer LoyaltyKeywords : Customer Engagement, Customer Satisfaction, Customer Loyalty